Cefepime/sulbactam combination as a treatment alternative for extended spectrum beta-lacatmase producing Enterobacterales: A multicentric study from India - Yamuna Devi Bakthavatchalam; Dhanalakshmi Solaimalai; Anand Ashok; Harthi Ragothaman; Soniya Krishnamoorthy; Nivedhana Subburaju; Sanjay bhattacharya; Rudresh Sm; Shripad Murlidhar Taklikar; Barney Isaac; Kamini Walia; Balaji Veeraraghavan (Elsevier, 2024)
Background: Piperacillin/tazobactam has limited activity against Enterobacterales, which concurrently express ESBL/ampC/OXA-1 beta-lactamases, which are widely prevalent in India. Thus, there is a severe dearth for carbapenem sparing options that aggravate more dependent carbapenem therapy. In the Indian market, various cefepime/BLI combinations in diiferent fixed ratios were introduced to clinical practice. We investigated the activity of cefepime with increased sulbactam ratios against contemporary isolates of ESBL/OXA-1 expressing Enterobacterales. Methods: Non-duplicate contemporary ESBL and/or OXA-1 expressing E. coli (n = 117) and K. pneumoniae (n = 71) isolates were included in this study. The MIC of cefepime/sulbactam and its comparators were determined using a broth microdilution method. The presence of ESBL and OXA-1 genes were identified using multiplex PCR. Results: Against ESBL and OXA-1 co-producing E. coli, cefepime combined with sulbactam at 8 mg/L, inhibited 82% of the isolates. Cefoperazone susceptibility against ESBL-E. coli increased from 52% at 4 mg/L to 77% at 8 mg/L with sulbactam. When tested against K. pneumoniae co-expressing ESBL and OXA-1, cefepime susceptibility was 77% at 4 mg/L sulbactam and 88% at 8 mg/L sulbactam. PTZ consistently showed limited activity against ESBL co-harbouring OXA-1 (E. coli, 43% and K. pneumoniae, 61%). Conclusion: The present study demonstrates that adding an increased sulbactam concentration enhances cefepime's activity against contemporary ESBL/OXA-1 expressing Enterobacterales. A reformulated cefepime/sulbactam (2 g/2 g) combination may be the best carbapenem sparing option until cefepime/tazobactam and cefepime/enmetazobactam become available in the future.